Mineral Reporting Standards: PERC’s Role in CRIRSCO and Its Relevance to the European Mining Sector - Edmund Sides; Ruth Allington (Earth Science, Systems and Society)
Modern society is heavily reliant on minerals to support current lifestyles and requires continued investment in the exploration, evaluation, development, and production of mineral raw materials. Potential investors and their advisors require reliable information to support decisions on investments in minerals projects. To address these needs, international guidelines and reporting standards have been developed. The Committee for Mineral Reserves International Reporting Standards (CRIRSCO) is an international association of fifteen regional organisations from around the world, which promotes best standards in international minerals reporting. The Pan-European Reserves and Resources Reporting Committee (PERC), the European member of CRIRSCO, is an association of six Europe-based professional organisations, including the Geological Society of London (GSL). CRIRSCO-aligned reporting standards, such as the PERC Reporting Standard, are based on common principles, rules and guidance, and include sixteen common definitions of key terms. A description of the CRIRSCO International Reporting Template, which provides the basis for the development and periodic updating of individual standards such as the PERC Reporting Standard, is provided. The different elements of the 2019 version of the CRIRSCO Template are described, together with a discussion of changes and additions made in the PERC Reporting Standard 2021 which is based on it. The need for continual development and enhancement of the CRIRSCO-aligned standards to address investor concerns such as the need for information on the environmental, social and governance (ESG) aspects of mineral projects, as well as greater rigour in defining competency requirements, is discussed. Reference is also made to the United Nations Framework Classification for Resources (UNFC) and its relationship with the CRIRSCO-aligned standards, including the proposed use of the UNFC in the European Union’s Critical Raw Materials Act (CRMA) and how the two systems could be used in a complementary manner to support the needs of both governments and investors in mineral companies.